A call for constructing a metric for monitoring CA-MRSA and other infectious diseases - Alaa Al Amiry (BMC, 2020)
Abstract The use of metrics is necessary for decision making when it comes to evaluating the need for interventions and improve healthcare delivery (Adams, Metrics: What Counts in Global Health, 2016). They inform policy makers on the scale of the problem in hand, and whether it's time to intervene. It quantifies the matter of interest and gives an indication whether the intervention taken was effective or not- as a means for monitoring and evaluation (Murray and Frenk, Lancet 371:1191-1199, 2008). This article advocates for a new metric by suggesting criteria to construct it, in order to provide a "value-based" measurement for CA-MRSA as a starting point for all infectious diseases. It also discusses challenges to this suggested approach.